The Need for Islamic Counseling Services for Couples with Marital Problems - Radhiya Bustan; Bagus Riyono; Rizqi Maulida Amalia; Zahrina Amelia (Tazkiya Journal of Psychology, 2024)
Every couple hopes for eternal married life until the end of life. However, various challenges faced them. The divorce rate in Indonesia is increasing. Based on an interview with the counselor of the Advisory Board for the Development and Preservation of Marriage (BP4), one of the leading causes is the lack of religious internalizing. So that couples need help to build family relationships that are blessed by Allah SWT, one of which is through counseling services with an Islamic psychology perspective. This study wants to empirically examine the description of the needs of married couples who have marital problems in obtaining Islamic counseling services. This study using a mixed method with an explanatory sequential design type. The data collection tool is a questionnaire which uses descriptive quantitative analysis. Survey was carried out using a google form to 205 married respondents with accidental sampling. Then, in-depth interviews were added to the three of them. The results showed that when facing problems in their marriage, more than 50% of respondents stated that they tried to think positively that they were able to face the problem, then looked for the best information and solutions, made self-introspection and increased worship. This explains the importance of focusing on individual strengths, from a spiritual aspect. Meanwhile, for responses related to seeking assistance from external source, only less than 50% of respondents. For this external source, most of the respondents prefer to discuss with their close person compared to professionals. When talking to external parties, they are also more likely to come to ustaz to obtain suggestions from the spiritual side compared to professionals such as counselors, psychologists and psychiatrists. It describes that the religious perspective serves as one of the important factors needed in solving any problems faced by married couples.